Pier Diego Siccardi (1880-1917) and the “Clinica del Lavoro” in the trench warfare - Riva, Michele Augusto; Caramella, Michela; Turato, Massimo; Cesana, Giancarlo (La Medicina del Lavoro, 2017)
Background: The year 2017 marks the centenary of the death of the Italian scientist Pier Diego Siccardi (1880-1917), one of Luigi Devoto’s assistants at the “Clinica del Lavoro” in Milan. Objectives: To commemorate Siccardi and to describe the activities of the physicians of the “Clinica del Lavoro” during World War I. Methods: A comprehensive analysis was conducted on scientific papers written by Pier Diego Siccardi and by other physicians belonging to the Clinica del Lavoro, in the period 1915-1918. Results: During the Great War, the Clinica del Lavoro became a military hospital, even though it indirectly maintained a role in Occupational Health, assisting women who had started to work to replace the men sent to the front. Devoto and his assistants were drafted as Army doctors, but continued their research activities while at the front; focusing on the diseases that affected the soldiers, mainly infections. Bleeding fevers and jaundice were endemic among Italian troops, but their etiology was unknown. Pier Diego Siccardi identified this syndrome as an infection caused by a spirochete, and was the first one to isolate the infectious agent. Siccardi prematurely died of the same disease as a consequence of a laboratory accident, which provided further confirmation for his research. Conclusions: The heroic life of Siccardi and his tragic death testify the important activities of the scientists of the “Clinica del Lavoro” in the years of the Great War.